2016
DOI: 10.1117/1.jmi.3.3.037001
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal registration of multiple three-dimensional echocardiographic recordings for enhanced field of view imaging

Abstract: The use of three-dimensional (3-D) echocardiography is limited by signal dropouts and narrow field of view. Data compounding is proposed as a solution to overcome these limitations by combining multiple 3-D recordings to form a wide field of view. The first step of the solution requires registration between the recordings both in the spatial and temporal dimension for dynamic organs such as the heart. Accurate registration between the individual echo recordings is crucial for the quality of compounded volumes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…3-D fusion by registration has been successfully applied to fuse 3-D data sets by several groups (Hill et al 2001;Grau et al 2007;Sra 2008;Gooding et al 2010;Szmigielski et al 2010;Rajpoot et al 2011b;Bersvendsen et al 2016;Danudibroto et al 2016;Peressutti et al 2017). However, on its own, registration is of limited value, because contributing data sets need to demonstrate a significant degree of overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-D fusion by registration has been successfully applied to fuse 3-D data sets by several groups (Hill et al 2001;Grau et al 2007;Sra 2008;Gooding et al 2010;Szmigielski et al 2010;Rajpoot et al 2011b;Bersvendsen et al 2016;Danudibroto et al 2016;Peressutti et al 2017). However, on its own, registration is of limited value, because contributing data sets need to demonstrate a significant degree of overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, the majority of them pre-clinical, have examined various M3DFE protocols. These studies have demonstrated improvements in parameters such as FOV, EBD, contrast, contrast-to-noise ratio (CNR), signal-to-noise ratio (SNR) and perception of imaging artifacts (Soler et al 2005;Szmigielski et al 2010;Rajpoot et al 2011b;Yao et al 2011;Carminati et al 2015;Danudibroto et al 2016;Punithakumar et al 2016a;Peressutti et al 2017). However, these studies also show areas for improvement-for example, in accurate alignment of the 3-D data sets and feasibility.…”
Section: Introductionmentioning
confidence: 99%